Effects of adding crude glycerin in concentrate and castration on fattening performance and production return from raising Anglo-Nubian crossbred goats - Simuang, Suphakon; Wattanachant, Chaiyawan; Ngampongsai, Wanwisa (Food Agricultural Sciences and Technology, 2024)
Effects of adding crude glycerin in concentrate diet and castration on feed intake, growth performance, carcass characteristics, and production return of fattening 50% Anglo-Nubian x 50% Thai native goats were determined. Twenty male goats aged 12-13 months with 25.16±1.99 kg initial live weight were allotted into 2 x 2 factorial arrangement in CRD in which factor A was the type of concentrate diet (diet with no crude glycerin (CG) addition and diet with 10% of CG), and factor B was castration (intact and castrated males). Atratum (Paspalum atratum) grass was fed ad libitum, while 2% of concentrate diet was provided daily for 90 days. From the study, goats received diet with 10% CG addition had higher dry matter intake (DMI) and average daily gain (ADG) than those received a control diet (P<0.05). Castrated group had higher DMI and ADG than the non-castrated group (P<0.05). Higher slaughter weight and chilled carcass weight were observed in goats received concentrate plus 10% CG or castration while the carcasses had a higher fat percentage than the control group. Fattening goats with diet plus 10% CG and castration showed the highest economic return, but fattening goats with diet plus 10% CG could be another option. This was due to not only the high economic return was noted, but it also reduced suffering of castration.